Aspects Regarding the Modelling and Optimization of the Transesterification Process through Temperature Control of the Chemical Reactor - Stanescu Ruxandra-Cristina; Leahu Cristian-Ioan; Soica Adrian (MDPI, 2023)
Currently, biofuels represent a solution for the European Union in the transportation sector in order to reduce the greenhouse gas (GHG) emissions and the dependency of fossil fuels. Biodiesel from vegetable oils is a solution for countries with low GDP per capita to strengthen the internal agriculture, provide jobs, and reduce the use of fossil fuels. In this study, we model and simulate a temperature regulator designed for the biodiesel transesterification process in a discontinuous batch reactor, using methanol and a homogenous basic catalyst. The simulation was based on the kinetical model of the transesterification reaction and the mathematical model of the reactor. We considered molar ratios of alcohol/oil of 6:1 and 9:1, respectively, to shift the reaction equilibrium towards the production of fatty acid methyl esters. In the design of the simulation, the methanol boiling point was considered a restriction, therefore, temperatures below 65 C were imposed. The results demonstrate that the increase in temperature results in a decrease in the reaction time and a higher yield, especially for the 6:1 molar ratio reaction, and that the optimum temperature for the batch reactor is of 60 C. Automatic control improves the performance and costs of production.
Keywords: biofuel; transesterification; reactor; temperature control